Cefuroxime pharmacokinetics and pharmacodynamics for intravenous dosage regimens with 750 mg or 1500 mg doses in healthy young volunteers. Issue 3 (20th January 2020) - Thønnings, Sara; Jensen, Klaus S.; Nielsen, Ninna B.; Skjønnemand, Martin; Hansen, Dennis S.; Lange, Kai H. W.; Frimodt-Møller, Niels
Abstract : Introduction. Cefuroxime is an important antibiotic to treat several serious infections. Rapid elimination through the kidneys and the variation in MICs of various susceptible pathogens such as Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus and Streptococcus pneumoniae give rise to dosing issues, especially in otherwise healthy patients. Aim. To investigate the probability of target attainment (PTA) for obtaining the optimal dosage regimens for cefuroxime in healthy young people. Methodology. Two weeks apart 750 and 1500 mg cefuroxime were administered as an intravenous bolus to 20 healthy volunteers (mean age: 27 years). Population modelling and simulation studies were done based on the obtained data for cefuroxime plasma concentration. Results. With a target value of time above MIC ( T >MIC ) greater than 50 % the simulations revealed that a PTA of >99 % is obtained for S. pneumoniae with a dosage regimen of 750 mg q12h. For E. coli and K. pneumoniae the PTA was <90 % even with the highest, simulated dosage of 1500 mg q6h. For S. aureus a dosage of 1500 mg q8h gave a PTA above 97 %. Conclusions. S. pneumoniae is most likely treatable with a two-daily dose of 750 mg cefuroxime. Not treatable are K. pneumoniae and E. coli . For S. aureus 1500 mg q8h constitutes an optimal dosing schedule.